Anatomy, histology and elemental profile of long bones and ribs of the Asian elephant (Elephas maximus) - Korakot Nganvongpanit (2018)
© 2016, Japanese Association of Anatomists. This study evaluated the morphology and elemental composition of Asian elephant (Elephas maximus) bones (humerus, radius, ulna, femur, tibia, fibula and rib). Computerized tomography was used to image the intraosseous structure, compact bones were processed using histological techniques, and elemental profiling of compact bone was conducted using X-ray fluorescence. There was no clear evidence of an open marrow cavity in any of the bones; rather, dense trabecular bone was found in the bone interior. Compact bone contained double osteons in the radius, tibia and fibula. The osteon structure was comparatively large and similar in all bones, although the lacuna area was greater (P < 0.05) in the femur and ulna. Another finding was that nutrient foramina were clearly present in the humerus, ulna, femur, tibia and rib. Twenty elements were identified in elephant compact bone. Of these, ten differed significantly across the seven bones: Ca, Ti, V, Mn, Fe, Zr, Ag, Cd, Sn and Sb. Of particular interest was the finding of a significantly larger proportion of Fe in the humerus, radius, fibula and ribs, all bones without an open medullary cavity, which is traditionally associated with bone marrow for blood cell production. In conclusion, elephant bones present special characteristics, some of which may be important to hematopoiesis and bone strength for supporting a heavy body weight.